Resource quantity and quality co‐limit consumer production in forest streams - Lee M. Demi; Phillip M. Bumpers; Wyatt F. Cross; Susan L. Eggert; John S. Kominoski; David W. P. Manning; Amy D. Rosemond; J. Bruce Wallace; Seth J. Wenger; Jonathan P. Benstead (Ecology, 2025)
Ecological theory predicts that consumers should be co‐limited by resource quantity and quality, given widespread consumer‐resource nutritional imbalances. We used 25 estimates of annual community secondary production (ACSP) of stream macroinvertebrates to assess the relative roles of basal resource quantity (leaf litter standing stock [LLSS]) and quality (% nitrogen and % phosphorus of leaf litter) in modulating patterns of production in forest streams. We also tested the effects of hypothesized indirect drivers (stream discharge and inorganic nutrient concentrations) on basal resource quality and quantity and secondary production. In the top model for ACSP, LLSS, and %P together explained 59% of its variation, providing strong evidence of co‐limitation by both resource quantity and quality. Mean annual stream discharge and stream water P concentration explained 75% and 43% of variation in LLSS and %P, respectively. Together, stream discharge and stream water P concentration explained 77% of the variation in ACSP, demonstrating a critical link between hypothesized indirect and direct (basal resources) drivers and ACSP. Our results are the first to demonstrate co‐limitation of ACSP and highlight several mechanisms by which drivers of anthropogenic global change, such as altered precipitation (stream discharge) and eutrophication, influence the productivity of animal communities in stream ecosystems.